AB0272 Anti-Rheumatic Treatment Is Not Associated with Reduction of Pentraxin 3 (PTX3) in Rheumatoid Arthritis (RA), Psoriatic Arthritis (PSA) and Ankylosing Spondylitis (AS). (15th July 2016) - Deyab, G.; Hokstad, I.; Agewall, S.; Lyberg, T.; Whist, J.E.; Smastuen, M.C.; Bottazzi, B.B.; Hjeltnes, G.G.; Meroni, P.L.; Hollan, I.
Abstract : Background: PTX3, an important component of the innate immune system, has been proposed as a useful biomarker of inflammation and cardiovascular (CV) risk, but its role in inflammatory rheumatic diseases (IRDs) is still uncertain [1, 2]. Objectives: The aim of this study was to examine if methotrexate (MTX) and/or anti-tumor necrosis factor treatment (anti-TNF) treatment reduced serum PTX3 (s-PTX3) levels in IRDs (RA, PsA and AS), and if s-PTX3 levels were related to other markers of inflammation and to endothelial function (EF). Methods: From the biobank of PSARA, an observational study, we examined samples from 114 IRD patients starting with either MTX or anti-TNF with or without MTX (anti-TNF±MTX) due to active disease, who completed a 6 months follow up. s-PTX3 (enzyme-linked immunosorbent assay), EF (finger plethysmography) and established inflammatory biomarkers were evaluated at baseline and after 6 weeks and 6 months of therapy. Results: The s-PTX3 levels in IRD and all the diagnostic subgroups were above the upper limit of the reference range. In contrast to established inflammatory markers, in particular C- reactive protein (CRP) and erythrocyte sedimentation rate (ESR) (all p-values <0.05), s-PTX3 levels did not change significantly after 6 weeks and 6 months of anti-rheumatic therapy (all p>0.2). The effect of MTX monotherapy and anti-TNF±MTX on s-PTX3 levels was similar. Changes in CRP, ESR and EF were not related to changes in s-PTX3 levels neither in univariate analyses nor in analyses adjusted for potential confounders. Conclusions: IRD patients have increased s-PTX3 levels, which, in contrast to other inflammatory markers, do not seem to improve within 6 months of therapy with MTX and/or anti-TNF. Thus, in theory, s-PTX3 might reflect a persisting immune process, even a causal factor of the inflammation, not inhibited by the standard anti-rheumatic treatment. Furthermore, even though PTX3 is thought to be a strong predictor of CV prognosis, it was not related to EF. References: Bottazzi, B., et al., An integrated view of humoral innate immunity: pentraxins as a paradigm. Annu.Rev.Immunol., 2010. 28: p. 157–183. Jylhävä, J., et al., Pentraxin 3 (PTX3) is associated with cardiovascular risk factors: the Health 2000 Survey. Clinical and Experimental Immunology, 2011. 164(2): p. 211–217. Disclosure of Interest: None declared